Molecular Docking Studies on The Anti-Cancer Activity of Novel Tri-Substituted Fluoro Indole Derivatives Against Human Topoisomerase-Ii Enzyme using In-Silico Methods - Shrestha, Sabin; Khanal, Dharma Prasad; Adhikari, Pharsuram; Thapa, Rahi Bikram; Maji, Rituparna (Journal of Manmohan Memorial Institute of Health Sciences, 2024)
Background: Cancer remains the leading cause of the death worldwide and expected that annual cancer case will rising very rapidly and make the scenario even more troublesome as well as Due to drug resistance makes things even worse.Method: Auto Dock 4.1 was used to evaluate selected tri-substituted fluoro indole molecules against human topoisomerase II and Discovery studio visualizer and marvin sketch was used to create 3D and 2D structure interaction. Tri-substituted fluoro indole derivatives were docked against the human topoisomerase II enzyme using in-silico methods and various web server was used to determine various parameters.Results: Docking studies revealed that tri-substituted fluoro indole derivatives could be a good alternate against human topoisomerase II as an anti-cancer agent. Molecular docking score scored by fludarabine [-7.6, -7.6, -8.6, -7.7] kcal/mol with nine hydrogen bonds, S-2 [-8.8, -7.7, -9.6, -8.7] kcal/mol with elveven hydrogen bonds, and S-14 showed [-9.2, -8.2, -8.6, -8.6] kcal/mol with twelve hydrogen bonds respectively in chain-A, B, C, D with excellent drug likeness, good pharmacokinetics parameters, mild toxicity in In-silico model reveals that Tri-substituted fluoro indole derivatives could be a good alternate against human topoisomerase II as an anti-cancer agent.Conclusion: Among twenty derivatives S-2 and S-14 showed potential inhibitory effect against 4R1F human topoisomerase II with excellent docking score, drug likeness, good pharmacokinetics parameters, mild toxicity in Insilco model.